Making and Remaking Silla Origins - McBride, Richard D. (JAOS, 2020)
The official narrative on the early history of the Korean state of Silla (trad. 57 BCE-935 CE) was constantly under revision and probably not initially charted until the late seventh or early eighth century. This narrative continued to evolve throughout the remainder of the Silla and early Koryŏ period (918-1392), achieving its final form in the mid-twelfth century with the publication of the Samguk sagi. King Mich'u (trad. r. 262-284) was modeled closely on King Pŏphŭng (r. 514-540) to push Silla origins back several hundred years. Sŏk T'arhae (trad. r. 57-80) and Naemul (trad. r. 356-402) were crafted based on Chinese historiography. The late emergence of the legend of Pak Hyŏkkŏse (trad. 57 BCE-4 CE) as the ultimate founder of Silla in the Koryŏ period reflects the relevance of the Pak descent group in the Silla-Koryŏ transition period and rise of the Pak lineage in the early Koryŏ period.